2009
DOI: 10.1056/nejmoa0902903
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Medulloblastoma with Hedgehog Pathway Inhibitor GDC-0449

Abstract: SUMMARY Medulloblastoma is the most common malignant brain tumor in children. Aberrant activation of the hedgehog signaling pathway is strongly implicated in the development of some cases of medulloblastoma. A 26-year-old man with metastatic medulloblastoma that was refractory to multiple therapies was treated with a novel hedgehog pathway inhibitor, GDC-0449; treatment resulted in rapid (although transient) regression of the tumor and reduction of symptoms. Molecular analyses of tumor specimens obtained befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
706
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 921 publications
(721 citation statements)
references
References 23 publications
10
706
0
5
Order By: Relevance
“…Taken together, these studies indicated that Hedgehog-Gli signaling pathway is critical for the GSC maintenance and targeting this pathway with pharmacologic inhibitors may inhibit GSC growth and improve the efficacy of conventional therapies against GBMs. Although the toxicity of these inhibitors on normal stem cells needs to be carefully evaluated, recent clinical studies with the Hedgehog inhibitor GDC-0449 have shown promising responses with acceptable toxicity in brain tumor patients (Rudin et al, 2009;Yauch et al, 2009). …”
Section: Hedgehog-gli Signalingmentioning
confidence: 99%
“…Taken together, these studies indicated that Hedgehog-Gli signaling pathway is critical for the GSC maintenance and targeting this pathway with pharmacologic inhibitors may inhibit GSC growth and improve the efficacy of conventional therapies against GBMs. Although the toxicity of these inhibitors on normal stem cells needs to be carefully evaluated, recent clinical studies with the Hedgehog inhibitor GDC-0449 have shown promising responses with acceptable toxicity in brain tumor patients (Rudin et al, 2009;Yauch et al, 2009). …”
Section: Hedgehog-gli Signalingmentioning
confidence: 99%
“…Similarly, cyclopamine is effective in reducing medulloblastoma development in Ptch1 þ /À mice (Sanchez and Ruiz i Altaba, 2005) as well as tumor growth of many cancer cell lines in nu/nu mice (Berman et al, 2002;Thayer et al, 2003;Karhadkar et al, 2004;Stecca et al, 2007 Table 2). Another clinical trial of GDC-0449 on a medulloblastoma patient also resulted in a rapid reduction of tumor (although transiently) but the drug resistance occurred because of SMO mutation Rudin et al, 2009). Recent results from mouse models indicate that the inhibition of Hh signaling has little effects on bone barrow stem cell population, which clears the concern of toxic effects of Hh signaling inhibition on normal stem cells Hofmann et al, 2009).…”
Section: Small-molecule Modulators Of Hedgehog Signalingmentioning
confidence: 99%
“…Small molecule inhibitors of the Hh pathway have recently been shown to exhibit antitumor activity in preclinical mouse models of Hh-driven cancers as well as in pilot clinical studies (Romer et al, 2004;Rubin and de Sauvage, 2006;Rudin et al, 2009;Von Hoff et al, 2009). It will therefore be important to identify those cancers or subgroups of patients that harbor constitutively elevated Hh signaling, as they will likely be susceptible to pathway inhibition.…”
Section: Introductionmentioning
confidence: 99%